Development of Arabic Language Learning Research: A Bibliometric Study on Scopus (2009-2024) - Ramadhan Safrudin; Ade Nandang; Sri Dewi Priwarti Siregar; Izzuddin Musthafa; Muhamad Fauzan Fauzi; Moch. Hazmi Farhanul Alby; Suyono Suyono (Universitas Islam Negeri Palangka Raya, 2024)
This study presents a bibliometric analysis of the development of Arabic language learning research indexed in the Scopus database from 2009 to 2024. The aim of this research is to identify trends, citation patterns, geographical distribution, and journal rankings. The method used is bibliometric analysis by collecting and analyzing data using VOSviewer and Publish or Perish software. The analyzed parameters include the number of publications, citation patterns, geographical distribution, h-index, g-index, and journal rankings. A total of 26 relevant publications were analyzed, showing Indonesia as the leader in the number of publications, followed by Malaysia and Tunisia. Significant international collaborations, especially among Indonesia, Malaysia, and Jordan, were identified. The most cited documents appeared in 2011 and 2019, with 2011 having the highest total citations of 20. The highest h-index and g-index values were recorded in 2019, each reaching three. Indonesia contributed 11 documents, Malaysia five documents, and Tunisia three documents. Most research was found in non-quartile journals, although Q1-ranked journals were also prominent. The main focuses in the development of Arabic language learning identified are e-Learning, bilingualism, and computational linguistics. This study maps the current landscape of Arabic language learning research, identifies key areas for future investigation, and encourages collaboration among scholars to advance Arabic language education globally.